2022
DOI: 10.1155/2022/7284068
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of Infection Factors in Secondary Internal Fixation after External Fixation for Open Fracture of a Long Bone: A Cohort of 117 Patients in a Two-Center Clinical Study

Abstract: Purpose. To investigate infection risk factors after secondary internal fixation (IF) of open fracture of a long bone with removed fixation frame and explore the safe range of feasible operation for abnormal inflammatory indicators. Methods. Clinical data of 117 cases of open fracture of a long bone that underwent temporary external fixation (EF) in one stage and IF in two stages were retrospectively analyzed. Collected data included age, sex, Gustilo type, multiple injuries, debridement time, duration of EF, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 35 publications
(37 reference statements)
0
13
0
Order By: Relevance
“…As shown in Figure 2, all studies 8–10,19–27 were of high quality. However, limitations in two studies 8,24 and findings and conflicts of interest were not reported in two studies 8,20 …”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…As shown in Figure 2, all studies 8–10,19–27 were of high quality. However, limitations in two studies 8,24 and findings and conflicts of interest were not reported in two studies 8,20 …”
Section: Resultsmentioning
confidence: 94%
“…Twenty‐three studies were removed owing to improper research design or outcomes, and 22 studies were discarded due to a lack of necessary data after carefully examining the full text of 55 studies. Finally, this systematic review and meta‐analysis included 12 studies 8–10,19–27 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations